Platform “Get Epic” Sebagai Perpustakaan Digital di Masa Pandemi Covid-19 - Agus Ervianto (Universitas Wijaya Kusuma Surabaya, 2022)
Research Purpose. The aim of this study is to provide an overview of the use of the Get Epic platform as a digital library during the Covid-19 pandemic in terms of its use, seen from its appearance, menus, and collections provided. Methods. The research method used in this study is the literature study method. The library study tool in this study was sourced from the Get Epic utilization report, which has been used by the Nation Star Academy Middle School library as a digital library platform, as well as scientific journals related to the use of digital libraries during the Covid-19 pandemic. Results and Discussion. The Covid-19 pandemic is not an obstacle for libraries to provide collections and carry out compulsory reading activities at schools—easy access to use the collection with smartphones is a solution for libraries to provide online reading resources. Get Epic's digital library also makes it easy for parents to see what their children read during activities at home. Conclusion. The application of Get Epic as a means of digital reading resources provides benefits in the Nation Star Academy Junior High School environment. Initially, the library had no visitors, and the library could carry out borrowers with the platform for one-year reading activities.Keywords: Online Learning, Covid-19, Digital Library, Get Epic